The sonar beam pattern of a flying bat as it tracks tethered insects - Ghose, Kaushik (2003)
This paper describes measurements of the sonar beam pattern of flying echolocating bats, Eptesicus fuscus, performing various insect capture tasks in a large laboratory flight room. The beam pattern is deduced using the signal intensity pattern from a linear array of microphones. The positions of the bat and insect prey are obtained by stereoscopic reconstruction from two camera views. Results are reported in the form of beam pattern plots and estimated direction of the beam axis. The bat centers its beam axis on the selected target with a standard deviation (σ) of 3°. The experimental error is ±1.4°. Trials conducted with two targets show that the bat consistently tracks one of the targets with its beam. These findings suggest that the axis of the bat sonar beam is a good index of selective tracking of targets and in this respect is analogous to gaze in predominantly visual animals.